Neonatal networks: clinical research and quality improvement. Issue 6 (December 2015) - Profit, Jochen; Soll, Roger F.
Summary: Worldwide, neonatal networks have been formed to address both the research and quality improvement agenda of neonatal–perinatal medicine. Neonatal research networks have led the way in conducting many of the most important clinical trials of the last 25 years, including studies of cooling for hypoxic–ischemic encephalopathy, delivery room management with less invasive support, and oxygen saturation targeting. As we move into the future, increasing numbers of these networks are tackling quality improvement initiatives as a priority of their collaboration. Neonatal quality improvement networks have been in the forefront of the quality movement in medicine and, in the 21st century, have contributed to many of the reported improvements in care. In the coming years, building and maintaining this community of care is critical to the success of neonatal–perinatal medicine.